Pain and Analgesia Requirements With Hip Fracture Surgery. (May 2017) - A'Court, Jamie; Lees, Deborah; Harrison, William; Ankers, Thomas; Reed, Mike R.
Abstract : BACKGROUND: Hip hemiarthroplasty and dynamic hip screw (DHS) fixation are common procedures performed in trauma units, but there is little information regarding perioperative pain experience with respect to these treatment modalities. PURPOSE: To evaluate the relationship between pain, analgesia requirements, and type of procedure for hip fracture surgery. METHODS: An analysis was performed on consecutive patients presenting with a hip fracture in 2 hospitals over 2 years. Patients with a diagnosis of dementia were excluded because of the limitations of pain assessment. Postoperative pain scores were taken from standardized patient observation charts. Perioperative opiate consumption was calculated from inpatient drug charts. RESULTS: A total of 357 patients were studied; 205 patients (53%) underwent a cemented hemiarthroplasty and 152 (47%) had fixation with a DHS. Patients who underwent a DHS fixation had more pain than those who had a hemiarthroplasty and required almost double the amount of opiates. CONCLUSION: The reason for the elevated pain scores and higher morphine requirement in the DHS group (DG) remains unclear. It could be related to highly sensitive periosteum reaction in the DG. It is important to recognize the difference in pain experienced between the groups, and analgesia should be tailored toward the individual based upon clinical assessment and knowledge of the surgery performed. A comprehensive understanding of this principle will allow for improved perioperative surgical care and patient experience.